Toward an Empowerment-Based Nursing Framework for Managing Multimorbidity in Older Adults - Argi Virgona Bangun; Minerva B. De Ala; Marietta Fabros; Marcus Ochoa (Poltekkes Kemenkes Surakarta, 2026)
Background: Population aging presents major challenges for healthcare systems, particularly in managing the complex needs of older adults with multiple chronic conditions (multimorbidity). This study explores behavioral, cognitive, and contextual factors influencing how older adults navigate complex treatment regimens, with the goal of developing an empowerment-based nursing framework. Methods: This sequential explanatory mixed-methods study involved 127 older adults with chronic conditions in the quantitative phase and 9 participants in the qualitative phase. In-depth semi-structured interviews were conducted with the qualitative subsample and analyzed using thematic analysis, generating codes and themes related to the contextual dynamics of health decision-making. Findings from both phases were integrated to develop an empowerment-based nursing framework, grounded in patient autonomy, shared decision-making, and relational support, aimed at strengthening older adults' capacity to manage multimorbidity effectively.I Results: Quantitative findings revealed that belief about medicine (β = 0.561, p = 0.001), health literacy (β = 0.219, p = 0.025), and perceived social support (β = 0.288, p = 0.001) significantly influenced care-related behaviours. The integration of findings underscored the need for tailored health education, supportive family engagement, emotionally responsive communication, and culturally accessible nursing care. Conclusion:Older adults managing multimorbidity make care-related decisions based on a complex interplay of beliefs, literacy, emotional readiness, and social context. Nurses must adopt a holistic, empowerment-based approach that strengthens both medical understanding and relational support. The proposed framework offers direction for nursing practice and policy to improve adherence, autonomy, and quality of care in geriatric populations.